Usefulness of the High Triglyceride-to-HDL Cholesterol Ratio to Identify Cardiometabolic Risk Factors and Preclinical Signs of Organ Damage in Outpatient Children - Di Bonito, Procolo (American Diabetes Association, 2012)
OBJECTIVE: To evaluate whether the high triglyceride-to-HDL cholesterol (TG-to-HDL-C) ratio is associated with cardiometabolic risk (CMR) factors and preclinical signs of organ damage in an outpatient population of white children and adolescents. RESEARCH DESIGN AND METHODS: The study population included 884 subjects (aged 6–16 years), of whom 206 (23%) were normal weight, 135 (15%) were overweight, and 543 (61%) were obese. Biochemical variables were analyzed in the whole sample, whereas homocysteine and left ventricular (LV) geometry and function were evaluated in 536 and 258 children, respectively. RESULTS: The percentage of pubertal children (P < 0.001), as well as measurements of BMI, waist circumference, homeostasis model assessment of insulin resistance, white blood cell count, alanine aminotransferase (ALT), systolic blood pressure (P < 0.0001, for all), creatinine (P < 0.001), and diastolic blood pressure (P < 0.02), increased from the lowest to the highest tertile of the TG-to-HDL-C ratio. Age, sex, homocysteine, and glomerular filtration rate did not change. Moreover, interventricular septum thickness, relative wall thickness, and LV mass index (P = 0.01 to P < 0.0001) increased across tertiles of the TG-to-HDL-C ratio. Children with a TG-to-HDL-C ratio ≥2.0 showed a two- to threefold higher risk of elevated ALT levels and concentric LV hypertrophy than those with a TG-to-HDL-C ratio <2.0, independent of confounding factors. CONCLUSIONS: The high TG-to-HDL-C ratio is associated with several CMR factors and preclinical signs of liver and cardiac abnormalities in the outpatient, white pediatric population. Thus, a TG-to-HDL-C ratio ≥2.0 may be useful in clinical practice to detect children with a worsened CMR profile who need monitoring to prevent cardiovascular disease in adulthood.